The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1109/taffc.2016.2631594
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Stress Detection from Multiple Assessments

Abstract: International audienceStress is a complex phenomenon that impacts the body and the mind at several levels. It has been studied for more than a century from different perspectives, which result in different definitions and different ways to assess the presence of stress. This paper introduces a methodology for analyzing multimodal stress detection results by taking into account the variety of stress assessments. As a first step, we have collected video, depth and physiological data from 25 subjects in a stressf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Previous studies have similarly proposed optimal HRV features for stress monitoring [10,11,12,13,14,15,16]. However, most of those studies considered a singular exposure to a specific stressor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have similarly proposed optimal HRV features for stress monitoring [10,11,12,13,14,15,16]. However, most of those studies considered a singular exposure to a specific stressor.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, a feature selection approach such as the filter [13,14] and wrapper method [13,15,16] was used for determining optimal HRV features. Aigrain et al [15] evaluated the predictive power of various multimodal features by investigating the composition of the best feature subset and showed that the HR values (maximum and variation) and the amplitude of HR (maximum, mean, and variation) provided the best prediction among features related to ECGs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…3e). Motion history images (MHI) have been proven to be very robust in detecting motion and is widely employed by various research groups for action recognition and motion analysis [9], [10]. Other processing techniques such as optical flow or dense face tracking will be considered in future work.…”
Section: Facial Featuresmentioning
confidence: 99%
“…However, most of these systems require invasive sensors that may themselves induce stress in participants. Recent advances in computer vision have led to the design of noninvasive systems capable of estimating user stress from the video analysis of facial expressions, gestures, postures, gaze and blinking, and head movements [9], [10], [11], [12]. Tasks and situations commonly used for the design and evaluation of these systems include mathematical problem solving, public speaking and global overwhelming workload.…”
Section: Introductionmentioning
confidence: 99%